FTIR spectroscopy of protein isolates of salt-tolerant soybean mutants - AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL; ATAK, ÇİMEN; ÇELİK, ÖZGE (Springer, 233 Spring St, New York, Ny 10013 USA, 2018)
The effect of salinity on the conformation of proteins of four salt-tolerant M-2 generation mutants of soybean plants (S04-05/150-2, S04-05/150-8, S04-05/150-106, and S04-05/150-114) was investigated using Fourier transform infrared (FTIR) spectroscopy. Salinity is one of the important abiotic stress factors that limits growth and productivity of plants. The mutants belonging to the M-2 generation were determined as tolerant to 90 mM NaCl. The relative contents of alpha-helix, beta-sheet, turn, and irregular conformations for the soybean protein isolates were determined depending on the analysis of the amide I region. The comparison of the secondary structures of soybean proteins of the mutants with those of the control group indicated that the alpha-helix structure percentage was diminished while beta-turn and disordered structures were increased as a result of the salt stress.
Keywords: IR spectroscopy; soybean protein isolates; salt-tolerant mutants; Infrared Amide Bands; Secondary Structure; Spectral Parameters; H2O Solutions; Polypeptides; Intensities; Expression